Educação e gênero: uma análise sobre o processo de expansão da participação de mulheres escolarizadas no mercado de trabalho brasileiro de 2003 a 2015 - PÓVOAS, Maysa Thaís Teixeira (2023)
Starting from the 2000s, affirmative actions have gained significant prominence on government agendas, garnering increasing popular support over time. This has contributed to social inequalities becoming a widely debated issue in Brazil. In the field of education, affirmative actions, both in the public sector through quotas and in the private sector through scholarships and student financing, adopted in recent decades, have facilitated the entry of historically excluded groups into higher education, thus contributing to the democratization of access to academic spaces. This dissertation aimed to describe and quantify the evolution of female participation with higher education in the Brazilian labor market from 2003 to 2015. It started from the hypothesis that the presence of women with higher education became more pronounced in the labor market after the expansion of public policies in higher education. As such, a theoretical-historical analysis was undertaken to understand the implementation process of affirmative actions in Brazil. Additionally, indicators obtained from official sources were analyzed, along with electronic journals, dissertations, and specialized works addressing the topic. The findings concluded that increased educational attainment has proven to be a significant factor in women's entry and persistence in the labor market, as well as enabling their participation in more diverse occupations. This progress reflects not only the consolidation of rights achieved over the years but also the positive impact of public policies aimed at democratizing access to higher education. Government reforms and programs have played a fundamental role in promoting gender equality of opportunities, facilitating greater female participation in the labor market.